A new species of freshwater flatworm (Platyhelminthes, Tricladida, Dendrocoelidae) inhabiting a chemoautotrophic groundwater ecosystem in Romania - Stocchino, Giacinta Angela; Sluys, Ronald; Kawakatsu, Mahasaru; Sarbu, Serban Mircea; Manconi, Renata (European Journal of Taxonomy, 2017)
We report the description of a new species of freshwater flatworm of the genus Dendrocoelum inhabiting the chemoautotrophic ecosystem of Movile Cave as well as several sulfidic wells in the nearby town of Mangalia, thus representing the first planarian species fully described from this extreme biotope. The species was also found in non-sulfidic wells localized in villages in the vicinity of the cave with a total of nine examined populations. Dendrocoelum obstinatum Stocchino & Sluys, sp. nov. represents the first triclad being able to live in both sulfidic and non-sulfidic waters. Among the fauna of the Mangalia sulfidic ecosystem it is the only species found also outside of the current boundaries of the sulfidic aquifer. One possible explanation of this peculiar distribution is that the new species is limited to the old boundaries of the sulfidic aquifer. The latter became much smaller during the hydrogeological history of the region, so that D. obstinatum may be considered to be an indicator of the extension of the sulfidic aquifer in the past of the Mangalia region. In the context of a biogeographic discussion on the distribution of the genus Dendrocoelum we provide an annotated checklist of species reported from Romania.